Significance of Load Balancing with Task Scheduling in Cloud Environment - Narwal, Abhikriti; Dhingra, Sunita (2025 4th International Conference on Computational Modelling, Simulation and Optimization (ICCMSO), 2025)
The term "cloud computing" involves working with a group of virtualized PC assets. A cloud can perform a range of functions comprising quick provisioning of physical or virtual machines, supporting repetitive, self-recovering, and highly adaptable programming models, and allowing tasks to recover from structure equipment/programming failures and rebalance distributions. The concept is to advance work area registration to a support-based stage by leveraging worker groups and huge database at datacentres. Task scheduling with load balancing has become interesting research in the space of cloud computing. By spreading work load across multiple nodes in the cloud system, a superior load balancing algorithm will improve performance and resource usage. The paper compares and contrasts enhanced multi-objective scheduling algorithm (EMOSA), the credit-based scheduling algorithm (CBSA), and the Enhanced Multi-Objective Scheduling algorithm with Load Balancing (EMOSA_LB) to find out the significance of load balancing with scheduling algorithms. Honey Bee based load balancing with scheduling technique ensures improved resource utilization with minimal response time, processing cost and processing time.